Cultural safety training for allied health students in Australia - Gray, Marion; Thomas, Yvonne; Bonassi, Marianne; Elston, Jacinta; Tapia, Geraldine (The Australian Journal of Indigenous Education, 2020)
Abstract Culturally safe health practitioners are essential for effective service provision to culturally diverse populations, including Indigenous Australians. Therefore, cultural safety education during training as a health care professional is an essential component in helping improve the health of Indigenous Australians. This study examined whether the implementation of an Indigenous cultural safety education workshop increased self-rated cultural safety knowledge and attitudes of allied health students. The study employed a quantitative before-and-after design using pre- and post-surveys to determine the level of attitudinal change in students who attended a day long workshop. The study sample consisted of 1st year (n = 347) and 4th year (n = 149) allied health students at a regional Australian university over the years 2007–2011. Whilst the results of this current study are varied in terms of achieving positive change across all of the taught items of knowledge and attitude, they provide some evidence around the value of this type of curriculum intervention in helping develop culturally safe practitioners. An important finding was around the student's becoming self-aware about their own values and cultural identity, combined with acknowledging the importance of this cultural identity to interactions with clients. This form of ‘cultural humility’ appears to be an important step to becoming a culturally safe practitioner. These types of interventions would be enhanced through embedding and scaffolding throughout the curricula.